Distributed anchor activation schemes for RSS localisation. (27th July 2022) - Ababneh, Ahmad A.; Al-Qudah, Zouhair
The activation of a well-chosen set of anchors for localisation is vital for preserving network energy and satisfying localisation error requirements. Herein, we propose two distributed anchor activation schemes for agent localisation employing received signal strength (RSS) measurements. The proposed schemes incorporate anchor energies, localisation error requirement and submodular behaviour of anchor activation on the localisation error. In the first scheme, a distributed probabilistic anchor activation scheme is proposed. An anchor is activated according to an evolving activation probability that is locally calculated. In the second scheme, activation is executed over a number of rounds with each round having its own activation threshold. A proposed dynamic model for an anchor's inclination to activate is compared against the round's threshold and an activation decision is made. Simulation results show the efficacy of the proposed schemes in satisfying the error requirement as well as decreasing energy consumption in the network and thereby extending its life.